Desenvolvimento de um procedimento operacional padrão (POP) sobre a punção do cateter venoso central totalmente implantado (CVC-TI) - Pereira, Jamile Mineu (2024)
Objective: To develop a standard operating procedure (SOP) on puncture of the fully implanted central venous catheter (CVC-TI). Method: To achieve this objective, two stages were developed: the first consisted of a scoping review on the care of the CVC-TI and the second of the development of the SOP on the care of the device. The scoping review was developed in accordance with the proposed JBI methodology and prepared in accordance with the recommendations of the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). The bibliographic search was carried out in the databases of the Regional Portal of the Virtual Health Library (LILACS, BDENF, ColecionaSUS and others), MEDLINE via PubMed, COCHRANE Library and the CAPES Periodicals Portal (CINAHL, SCOPUS, Web of Science and EMBASE ). The search results were imported into the Rayyan software and the selection of studies was based on the eligibility criteria and carried out by two independent collaborators. There was no definition of period and the languages were English, Portuguese and Spanish. The initial corpus of the search without duplications was 4127 manuscripts for the title and abstract reading phase, of which 3833 were excluded because they did not meet the inclusion criteria. Based on the criteria used, 115 articles were included for full analysis. From the compilation, it was divided into three thematic categories: Skin antisepsis; CVC-TI maintenance care; and care regarding complications related to CVC-TI. Based on the results of the review, the SOP on care during CVC-TI puncture was created and an analysis process was carried out by judges according to the collective wisdom method. The scale used is dichotomous; from this, 95% confidence intervals were calculated for the proportions of positive attribution by the judges. To organize the evaluated items, a table was created in Microsoft Excel to compile the judges' responses. The calculation of proportions and their confidence intervals were calculated in the SPSS program and the cutoff point used was the proportion of 80%. Results: Based on the compilation of the scoping review on CVC-TI care, the SOP was divided into pre-puncture care, puncture care and post-puncture care. The judges were selected using the intentional non-probabilistic sampling technique, followed by the snowball sampling technique. 20 judges were invited, of which 18 agreed to participate in the research, and the timely feedback was completed by 13 judges, of which 10 had a beginner proficiency level (76.9%) and 3 (23.1%) had an advanced beginner level. The judges received the SOP via email and the evaluation instrument via Google Forms. The judges' suggestions that obtained an agreement rate lower than 80% were modified, as well as some suggestions with an agreement rate higher than 80% that helped to refine the SOP. Conclusion: The improvement of the SOP after analysis by the judges brought important refinements to assist the Nurse in the safe management of the CVC-TI, making the SOP suitable for use in the clinical practice of the Oncology Nurse. DESCRITORS: Neoplasms, Catheters, Indwelling, Catheters, Central Ven